THE IMPORTANCE OF URBAN DESIGN GUIDELINES FOR TRANSIT-ORIENTED DEVELOPMENT, THE CASE OF THE UNIVERSITY BELT, MANILA CITY - R. Giron, Gene Lambert; Punnoi, Nattapong (Journal of Surveying, Construction and Property, 2025)
The University Belt, known for its agglomeration of educational institutions, faces rapid urbanization, rising population densities, and poverty rates. With the National Building Code of the Philippines outdated and the Manila Zoning Ordinance baseless due to the lack of a Comprehensive Land Use Plan, the University Belt showcased increased developments, converting low-population, low-building-density areas into unregulated high-population, high-density areas with condominiums, apartments, lodging, and commercial establishments. Without action, the University Belt and its urban development will become even more uncontrolled. The research argues that an Urban Design Guideline will regulate development and redevelopment in the study area and foster control. Thus, this paper seeks first to understand the urban growth and development trend that led to the current condition of the University Belt, determine why the University Belt continues to promote an uncontrolled and unregulated neighborhood despite having governing policies for architecture practitioners, and synthesize architecture practitioners' insights on the governing urban development control policies to highlight the possible need for Through foot and windshield surveys, GIS mapping, a careful study of available datasets, and a survey, the site's context was fully understood and analyzed. In this research, a stratified random sampling approach using a normal distribution with 397 architecture practitioners in the study area found that those who observe urban development controls lack the confidence and relevance to follow it. This research emphasizes the importance of an Urban Design Guideline because it will consolidate all issues of compatibility, frequency, specificity, and harmony of applicable urban development controls in the University Belt to create a high-quality, livable environment ready for transit-oriented development.